IDENTIFIKASI MUTU ASAP CAIR HASIL PIROLISIS LIMBAH TANDAN KOSONG KELAPA SAWIT - Eva Ramalia Sari (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2018)
One application of clean production in the oil palm industry is the processing of solid waste such as empty fruit bunches (EFB) into liquid smoke. This research tried to do pyrolysis of EFB followed by redestilation process produce liquid smoke. The purpose of this research is to identify the quality of liquid smoke produced by pyrolysis process of EFB and redestilation. EFB are pyrolysis process at 400oC for 3 hours. Liquid smoke pyrolysis results are redistilled twice at 145oC. Liquid smoke quality data was quantitative descriptive analyzed. The results showed that the liquid smoke produced by pyrolysis process of empty fruit bunches has pH 3.20, phenol content of 6.85%, acetic acid level of 16.45%, and tar level of 2.96% (classified as grade 2) which can be used as a food preservative.